Tyrosine phosphorylation of a receptor‐like cytoplasmic kinase, BSR1, plays a crucial role in resistance to multiple pathogens in rice. (20th October 2018) - Sugano, Shoji; Maeda, Satoru; Hayashi, Nagao; Kajiwara, Hideyuki; Inoue, Haruhiko; Jiang, Chang‐Jie; Takatsuji, Hiroshi; Mori, Masaki
Summary: Plants have evolved many receptor‐like cytoplasmic kinases (RLCKs) to modulate their growth, development, and innate immunity. Broad‐Spectrum Resistance 1 ( BSR1 ) encodes a rice RLCK, whose overexpression confers resistance to multiple diseases, including fungal rice blast and bacterial leaf blight. However, the mechanisms underlying resistance remain largely unknown. In the present study, we report that BSR1 is a functional protein kinase that autophosphorylates and transphosphorylates an artificial substrate in vitro . Although BSR1 is classified as a serine/threonine kinase, it was shown to autophosphorylate on tyrosine as well as on serine/threonine residues when expressed in bacteria, demonstrating that it is a dual‐specificity kinase. Protein kinase activity was found to be indispensable for resistance to rice blast and leaf blight in BSR1 ‐overexpressing plants. Importantly, tyrosine phosphorylation of BSR1 was critical for proper localization of BSR1 in rice cells and played a crucial role in BSR1‐mediated resistance to multiple diseases, as evidenced by compromised disease resistance in transgenic plants overexpressing a mutant BSR1 in which Tyr‐63 was substituted with Ala. Overall, our data indicate that BSR1 is a non‐receptor dual‐specificity kinase and that both tyrosine and serine/threonine kinase activities are critical for the normal functioning of BSR1 in the resistance to multiple pathogens. Our results support the notion that tyrosine phosphorylation plays a major regulatory role in the transduction of defense signals from cell‐surface receptor complexes to downstream signaling components in plants. Significance Statement: BSR1, encoding a rice receptor‐like cytoplasmic kinase, confers resistance to multiple diseases when overexpressed in rice. However, the mechanisms underlying this resistance remain largely elusive. We show that BSR1 is a dual‐specificity kinase that phosphorylates both tyrosine and serine/threonine residues and that tyrosine phosphorylation of BSR1 plays a crucial role in BSR1‐mediated resistance to multiple diseases.